Development of a Mobile-Based Thesis Examination Assessment Application Using the Mobile-D Method - Agra Sanrio (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2025)
This study aims to improve the effectiveness of thesis examination assessment management, which includes proposal examinations and comprehensive examinations, through the development of a mobile-based assessment application. The primary issue motivating this research is the irregularity of examination administration, particularly during online examinations implemented during the COVID-19 pandemic. This condition created the need for a system capable of ensuring accurate dissemination of examination schedules, accelerating the assessment process, and organizing examination data recording in a structured manner. The application was developed on the Android platform because this technology is predominantly used by students and lecturers at Universitas Bina Darma. The system development process employed the Mobile-D method, which consists of five stages: Explore, Initialize, Productionize, Stabilize, and System Test and Fix. However, this research was limited to the first four stages, up to the Stabilize stage. The development process involved designing the system architecture and modeling, verifying user requirements and converting them into user interface designs, implementing the application in accordance with user needs, integrating application components, and conducting functional testing. The final outcome of this research is a thesis examination assessment application that supports a faster, more structured, and more efficient academic evaluation process.